The impact of mobilization protocols on the length of postoperative hospitalization among cardiac surgery patients - V. V. Vitomskyi; O. B. Lazarieva; E. Yu. Doroshenko; M. V. Vitomskа; T. М. Kovalenko; A. М. Hertsyk; S. V. Gavreliuk (Zaporožskij Medicinskij Žurnal)
The aim. To determine the impact of implementing the extra early mobilization protocol (EEM) on the length of intensive care unit (LICU) stay and postoperative unit (LPOU) stay and to assess the role of age, heart contractility, functional class and surgical outcomes.